PPAR/RXR Regulation of Fatty Acid Metabolism and Fatty Acid 𝜔-Hydroxylase (CYP4) Isozymes: Implications for Prevention of Lipotoxicity in Fatty Liver Disease - James P. Hardwick; Douglas Osei-Hyiaman; Homer Wiland; Mohamed A. Abdelmegeed; Byoung-Joon Song (PPAR Research)
Fatty liver disease is a common lipid metabolism disorder influenced by the combination of individual genetic makeup, drug exposure, and life-style choices that are frequently associated with metabolic syndrome, which encompasses obesity, dyslipidemia, hypertension, hypertriglyceridemia, and insulin resistant diabetes. Common to obesity related dyslipidemia is the excessive storage of hepatic fatty acids (steatosis), due to a decrease in mitochondria 𝛽-oxidation with an increase in both peroxisomal 𝛽-oxidation, and microsomal 𝜔-oxidation of fatty acids through peroxisome proliferator activated receptors (PPARs). How steatosis increases PPAR𝛼 activated gene expression of fatty acid transport proteins, peroxisomal and mitochondrial fatty acid 𝛽-oxidation and 𝜔-oxidation of fatty acids genes regardless of whether dietary fatty acids are polyunsaturated (PUFA), monounsaturated (MUFA), or saturated (SFA) may be determined by the interplay of PPARs and HNF4𝛼 with the fatty acid transport proteins L-FABP and ACBP. In hepatic steatosis and steatohepatitis, the 𝜔-oxidation cytochrome P450 CYP4A gene expression is increased even with reduced hepatic levels of PPAR𝛼. Although numerous studies have suggested the role ethanol-inducible CYP2E1 in contributing to increased oxidative stress, Cyp2e1-null mice still develop steatohepatitis with a dramatic increase in CYP4A gene expression. This strongly implies that CYP4A fatty acid 𝜔-hydroxylase P450s may play an important role in the development of steatohepatitis. In this review and tutorial, we briefly describe how fatty acids are partitioned by fatty acid transport proteins to either anabolic or catabolic pathways regulated by PPARs, and we explore how medium-chain fatty acid (MCFA) CYP4A and long-chain fatty acid (LCFA) CYP4F 𝜔-hydroxylase genes are regulated in fatty liver. We finally propose a hypothesis that increased CYP4A expression with a decrease in CYP4F genes may promote the progression of steatosis to steatohepatitis.